2011
DOI: 10.1007/s00418-011-0869-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition by quercetin triggers macroautophagy and blocks mTOR activity

Abstract: The bioflavonoid quercetin has long been known to exert anti-tumor effects, although the underlying mechanisms remain unknown. Investigation of the potential interference of this anti-oxidant with the efficacy of cell stress-inducing anti-cancer drugs revealed extensive intracellular vacuolation induced by quercetin in epithelial cancer cells that led to cell cycle arrest and ensuing apoptosis. Accumulation of biomarkers of autophagy, including fluorescent autophagy markers and acidotropic dyes characterized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 36 publications
1
50
0
1
Order By: Relevance
“…Meanwhile, competitive crosstalk between the ubiquitin-proteasome system and autophagy has also been recently reported. For example, when quercetin inhibited proteasomal activity, polyubiquitinated protein aggregates were accumulated and autophagy was increase via marked reduction in the phosphorylation of the mTOR substrates [21,22]. These results suggested that quercetin can be an autophagy inducer.…”
Section: Discussionmentioning
confidence: 64%
“…Meanwhile, competitive crosstalk between the ubiquitin-proteasome system and autophagy has also been recently reported. For example, when quercetin inhibited proteasomal activity, polyubiquitinated protein aggregates were accumulated and autophagy was increase via marked reduction in the phosphorylation of the mTOR substrates [21,22]. These results suggested that quercetin can be an autophagy inducer.…”
Section: Discussionmentioning
confidence: 64%
“…Pharmacologically induced proteasome inhibition upregulates autophagy in mouse cardiomyocytes, 196 human prostate cancer cells, 197 and human breast cancer cells. 198 In mouse fibroblasts, autophagy is activated by selective blockage of chaperone-mediated autophagy. 199 Similarly, knockdown of an essential autophagy gene (ATG5) results in upregulation of chaperone-mediated autophagy in mouse embryonic fibroblasts.…”
Section: Model Of Controlmentioning
confidence: 99%
“…Also, inhibition of autophagic degradation can often lead to the accumulation of LC3-II proteins [94]; however, in all the above-cited papers rapidly activated autophagy after proteasome inhibition was observed [75,85]. The presence of a considerably increased number of autophagosomes at various stages was postulated as the most convincing proof of active ongoing autophagy after proteasome inhibition by different groups of proteasome inhibitors [24,88,91,[95][96][97].…”
Section: Direct Effects Of Proteasome Inhibition On Autophagy Markersmentioning
confidence: 99%